CLL, A RARE BUT TREATABLE CAUSE OF LONGITUDINALLY EXTENSIVE MYELITIS. Issue 12 (15th November 2016) - Ahmed, Wail; Coe, James; Carroll, Liam; Vundavalli, S; Chevassut, Timothy; Saha, Romi
Abstract : A 65-year-old lady presented with a 1-year history of progressive sensory and motor symptoms in the the legs, back pain, pruritus and night sweats. Neurological examination of the cranial nerves and upper limbs was unremarkable. Lower limb examination revealed mild bilateral spastic paraparesis. Cervical, axillary and inguinal lymphadenopathy was noted. Bloods showed only a mild lymphopenia. MRI revealed symmetrically diffuse nodular enhancement in the brain and longitudinally extensive transverse myelitis in the cervical and thoracic spine with leptomeningeal enhancement. CSF analysis showed a protein of 1888 mg/L, WBC 164 X 10/L (99% lymphocytes). Upon immunophenotyping, 14% of the lymphoid population were CD5/19+ or CD79b. A bone marrow biopsy showed PAX 5 and CD20 positive lymphocytes in keeping with chronic lymphocytic leukaemia (CLL). Results from ultrasound guided biopsy of left axillary lymph node were also in keeping with CLL/small lymphocytic lymphoma (SLL). Treatment with high dose Methotrexate, Cytrabine and Rituximab resulted in remarkable clinical and radiological improvement. CLL/SLL presenting with neurological symptoms is extremely rare and as far as we know this case is the first in which longitudinally extensive transverse myelitis and extensive brain white matter changes have been an initial manifestation of the disease.